2002
DOI: 10.1182/blood.v99.7.2448
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI deficiency in French Basques is caused predominantly by an ancestral Cys38Arg mutation in the factor XI gene

Abstract: Inherited factor XI deficiency is an injuryrelated bleeding disorder that is rare in most populations except for Jews, in whom 2 mutations, a stop mutation in exon 5 (type II) and a missense mutation in exon 9 (type III), predominate. Recently, a cluster of 39 factor XI-deficient patients was described in the Basque population of Southwestern France. In this study, we determined the molecular basis of factor XI deficiency in 16 patients belonging to 12 unrelated families of French Basque

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 40 publications
6
108
1
Order By: Relevance
“…7 Mutations were introduced into the pcDNA3 vector using the QuickChange TM site-directed mutagenesis kit (Stratagene, La Jolla, CA, USA) according to the manufacturer's instructions, using specific primers whose sequences are available upon request (seligson@sheba.health.gov.il). Baby hamster kidney (BHK) cells were grown in DMEM supplemented with 2 mg/mL L-glutamine and 5% fetal calf serum (Biological Industries, Beit-Haemek, Israel).…”
Section: Expression Of Wild Type or Mutant Fxi In Baby Hamster Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Mutations were introduced into the pcDNA3 vector using the QuickChange TM site-directed mutagenesis kit (Stratagene, La Jolla, CA, USA) according to the manufacturer's instructions, using specific primers whose sequences are available upon request (seligson@sheba.health.gov.il). Baby hamster kidney (BHK) cells were grown in DMEM supplemented with 2 mg/mL L-glutamine and 5% fetal calf serum (Biological Industries, Beit-Haemek, Israel).…”
Section: Expression Of Wild Type or Mutant Fxi In Baby Hamster Kidneymentioning
confidence: 99%
“…4 Two less common mutations were described in Jews: type I, a splice-site mutation and type IV, a 14bp deletion between exon 14 and intron N. 5,6 Other relatively frequent mutations, C38R and C128X, were reported in French Basques and Britons, respectively. [7][8][9] More than 120 other sporadic mutations have been identified in different populations [http://www.med.unc.edu/isth, http://www.factorXI.org]. 10 Characterization of the growing number of FXI mutations has shed light on the relationship between structure and function of this protein, and has contributed to defining the importance of its various domains.…”
mentioning
confidence: 99%
“…Haplotype analysis showed these three factor XI gene mutations were derived from distinct founders. Furthermore, these mutations have become useful tools in tracing the racial/genetic relationships in different populations [8]. Interestingly, the Gln263!Term mutation identified in this study has been reported twice in two Japanese kindreds [6,7].…”
Section: Discussionmentioning
confidence: 69%
“…However, the Glu117!Term mutation (type II mutation) has been observed in multiple kindreds of Ashkenazi Jew, Iraqi Jews, and Palestinian Arabs, and the Phe283!Leu mutation (type III mutation) has been observed in Ashkenazi Jews [8]. More recently, a Cys38!Arg mutation has also been observed in many French Basque kindreds [8]. Haplotype analysis showed these three factor XI gene mutations were derived from distinct founders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation